Depression, Anxiety and Their Correlates Among Patients With HIV in South Ethiopia: An Institution-Based Cross-Sectional Study - Duko, Bereket; Toma, Alemayehu; Asnake, Solomon; Abraham, Yacob (Frontiers in Psychiatry, 2019)
Background: Depressive and anxious symptoms are more regularly seen in HIV-infected people than in the general population. This investigation planned to evaluate the magnitude and factors related to depressive and anxiety symptoms among HIV patients in South Ethiopia, 2018. Methods: This was an institution-based cross-sectional study directed among 363 HIV-infected individuals who had a customary visit at Hawassa University Comprehensive Specialized Hospital and Yirgalem Hospital, Ethiopia, who were incorporated into the study through systematic sampling techniques. The hospital anxiety and depression scale (HADS) was utilized to take a look at anxious and depressive symptoms. Results: The mean age of the respondents was 37.66 years (SD ±10.03). The prevalence of depression and anxiety were 32.0% and 34.4%, respectively. Patients who were living alone [AOR = 1.94, (95% CI: 1.06, 3.56)], had poor social support [AOR = 5.57, (95% CI: 1.20, 10.84)] or had HIV-related perceived stigma [AOR = 2.35, (95% CI: 1.44, 3.84)] were more likely to have depression as compared to their counterparts. Those with a previous history of mental illness [AOR = 3.36, (95% CI: 1.31, 8.61)] and poor social support [AOR = 6.67, (95% CI: 1.47, 10.33)] were more likely to have anxiety symptoms. Conclusion: The prevalence of anxiety and depression in the current study was high. Concerned health departments of the country should create guidelines to screen and treat depression and anxiety among HIV patients. Further research on hazard factors of depression and anxiety ought to be examined to strengthen and expand these findings.